Aircraft observations and sub‐km modelling of the lake–land breeze circulation over Lake Victoria. (27th October 2021) - Woodhams, Beth J.; Barrett, Paul A.; Marsham, John H.; Birch, Cathryn E.; Bain, Caroline L.; Fletcher, Jennifer K.; Hartley, Andrew J.; Webster, Stuart; Mangeni, Solomon
Abstract: The lake–land breeze circulation over Lake Victoria was observed in unprecedented detail with a research aircraft during the HyVic pilot flight campaign in January 2019. An evening and morning flight observed the lake and land breezes respectively under mostly dry conditions. The circulation was observed at various heights along a transect across the lake and onshore in Tanzania. Profiles of the lower troposphere were recorded by dropsondes over the lake and land. Convection‐permitting MetUM simulations with different horizontal grid‐spacings (including sub‐km) were run for the flight periods. During the evening flight, the aircraft crossed the lake breeze front over land at 1627 LT, approximately 50 km to the east of the lake shore, recording a 6 g · kg − 1 decrease in specific humidity and reversal in wind direction over ∼ 5 km. During the morning flight, a shallow land breeze was observed across the eastern shore at 0545 LT. At least one region of increased and deeper moisture (previously seen in simulations but never observed) was sampled over the lake surface between 0527 and 0855 LT. This bulge of moisture was likely formed from the lifting of near‐surface moist air above the lake by low‐level convergence. The observations and model simulations suggest that low‐level convergence occurred at the leading edge of the land breeze, which had detached from the main land breeze and independently propagated westward across the lake with wave‐like characteristics. The MetUM simulations were able to reasonably reproduce the lake breeze front, bulge feature, and its propagation, which is a major achievement given the sparse observational data for model initialisation in this region. However, some timing, resolution and boundary‐layer depth biases require further investigation. Overall, this pilot campaign provided an unprecedented snapshot of the Lake Victoria lake–land breeze circulation and motivates a more comprehensive field campaign in the future. Abstract : Lake Victoria (pictured) is a hotspot for severe convective storms which pose a great danger to users of the lake. A research aircraft was flown over the lake to sample the lake–land breeze circulation largely responsible for these deadly storms. Lake and land breezes were observed across the eastern shore of the lake in evening and morning flights respectively. A bulge of moisture, likely formed by the uplift of moist near‐surface air by a propagating detached land breeze front, was observed.